INTERFERENCE IN THE FORMATION OF LINGUOCULTUROLOGICAL COMPETENCE IN TEACHING CHINESE - D.M. Juraev (Scholar Express Journal, 2021)
The issues related to formation of linguocultural competences of students studying Chinese were discussed in this article. The fact that integrated teaching of Chinese language and culture provides students with more opportunity to learn the national culture of China has been proved by the author
Keywords: China; language; culture; student